Environmental Uncertainty in the Influence of Strategic Change on Financial Performance - Triyonowati, Triyonowati; Rahayu, Rika; Zahro, Mar'atus; Maryam, Dewi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The increasingly competitive business environment has a negative impact on company performance. Companies are expected to create strategic competitiveness to maintain their competitive advantage and sustain their performance. Strategic change is a company's effort to adapt to a competitive environment. Additionally, changes in the external environment create environmental uncertainty, which can further deteriorate company performance. Therefore, strategic change becomes the primary choice for companies to improve performance when environmental uncertainty increases. This study aims to analyze the effect of strategic change on company performance and the role of environmental uncertainty in moderating this relationship. Using purposive sampling, this study utilizes data from 503 manufacturing companies that are listed on the Indonesia Stock Exchange from 2016 to 2020. Multiple linear regression and moderated regression analyses are employed as the analytical techniques. The results of this study indicate that strategic change has a positive and significant effect on company performance, and environmental uncertainty strengthens this influence.